2017
DOI: 10.1016/j.molimm.2017.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Inducible turnover of optineurin regulates T cell activation

Abstract: Optineurin (Optn) is an adaptor protein with homology to NF-κB essential-modulator (NEMO), the regulatory subunit of the IκB kinase (IKK) complex. Dysregulation of Optn has been linked to neurodegenerative, autoimmune and bone diseases. Optn shares a high degree of homology with NEMO, but is not part of the same high-molecular weight complex containing IKKα and IKKβ. Despite its homology with NEMO and the fact that it has been the subject of extensive study in several cell types, there are no published studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Optineurin directly competes with NEMO for the binding to ubiquitylated RIP ( 33 ) and recruits CYLD, which deubiquitinates RIP to inhibit NF-κB activation ( 40 ). Recently, it was shown that activation of T-cell receptor signalling triggers the degradation of optineurin to overcome optineurin’s negative regulation of NF-κB signalling, which acts to suppress T-cell activation ( 59 ). Interestingly, NF-κB upregulates OPTN expression ( 60 ), suggesting a negative feedback loop exists to ensure proper regulation of NF-κB signalling.…”
Section: Role Of Optineurin In Signalling and Intracellular Traffickimentioning
confidence: 99%
“…Optineurin directly competes with NEMO for the binding to ubiquitylated RIP ( 33 ) and recruits CYLD, which deubiquitinates RIP to inhibit NF-κB activation ( 40 ). Recently, it was shown that activation of T-cell receptor signalling triggers the degradation of optineurin to overcome optineurin’s negative regulation of NF-κB signalling, which acts to suppress T-cell activation ( 59 ). Interestingly, NF-κB upregulates OPTN expression ( 60 ), suggesting a negative feedback loop exists to ensure proper regulation of NF-κB signalling.…”
Section: Role Of Optineurin In Signalling and Intracellular Traffickimentioning
confidence: 99%
“…The OPTN gene (optineurin; MIM#602432) is localized on chromosome 10 at 10p13, encoding the protein optineurin which regulates vesicular transport [170] and NF-KB signaling [171]. Wong and Holzbaur [172] found, using live-cell microscopy, that optineurin is recruited to impaired mitochondria after PARKIN recruitment and stabilised via ubiquitin binding to ABIN and NEMO (UBAN) domain and eventually recruits LC3 via its LIR domain, leading to autophagosome formation.…”
Section: Optnmentioning
confidence: 99%
“…A mutant version of OPTN that fails to recruit CYLD to inhibit NF-κB activation in response to TNF is also unable to inhibit IRAK-1-induced NF-κB signaling ( 12 , 13 ). Finally, OPTN was recently shown to suppress T cell receptor-induced NF-κB activation and TNF production, in a manner dependent on ubiquitin-binding ( 14 ).…”
Section: Optn and Nuclear Factor-κb (Nf-κb) Signalingmentioning
confidence: 99%